Leadership Training untuk Mengasah Kemampuan Intrapersonal dan Interpersonal dalam Berorganisasi - Rahma Qudsi; Aulia Sthephani; Dina Safitri (Community Education Engagement Journal, 2019)
The activity aims to improve the intrapersonal and interpersonal skills of the members of Gema Kosgoro organization, located at Tangkerang Labuai Sub-District, Bukit Raya District, Pekanbaru City, and provide the opportunities for this organization in various educational and training programs to improve this ability. Based on the results of interviews, we have gotten some informations that the majority of Kosgoro members do not know about the benefits of intrapersonal and interpersonal communication. This is caused by the absence of opportunities to obtain communication knowledge such as interpersonal and intrapersonal social organization. Many facilities to get the information are made the chairman of the Gema Kosgoro Student Movement interest in conducting interpersonal and intrapersonal training in this organization. This dedication is given in the form of giving material and question and answer. The material given discusses intrapersonal and interpersonal communication in detail by the speakers. Then the next material is questions and answers which aimed to make participants understand more deeply about the material. This activity was carried out in the even semester T.A 2018/2019.